Konflik batin tokoh dalam novel Laut Bercerita - Ani Azzara; Indri Rahayu; Siti Fitriati; Ani Diana (BADAN PENERBIT STIEPARI PRESS, 2024)
Differences in each person's character cause conflict in life. This conflict can occur between people or within themselves, known as inner conflict. Such as the inner conflict experienced by the characters in the novel Laut Bercerita. The focus of this research can be located on the internal conflict depicted by the characters in the novel Laut Bercerita. The purpose of this research is to explain the types and reasons for internal conflict. This research is descriptive qualitative in nature. This research uses a descriptive analysis approach. Words, sentences and conversations are the data sources for this research. which is related to the internal conflict discussed in the book Sea Tells. The data source used is the novel Laut Bercerita.